Teaching basic statistics to blind students - Chou Chen, Shu Wei (2017)
Understanding statistics has become extremely important not only for researchers but also for the general public in order to understand publications that include statistical analysis. Having in mind promoting statistical literacy, teaching statistics to students not pursuing a career in statistics is a great challenge for any teacher. However, it is a much greater challenge when some of those students have visual impairment. This challenge was undertaken by the first author while teaching two statistics courses to Henry Martínez-Hernández, a totally blind student doing a biology major at the University of Costa Rica (UCR), in the second semester of 2014 and the first semester of 2015. We describe this experience and give some recommendations based on what we learned after evaluating the results.